Influence of Dyslipidemia on the Quality of Sexual Life in Women in the Menacme using a Combined Oral Contraceptive - Rodolfo Strufaldi; Luciano Melo Pompei; Marcelo Luis Steiner; César Eduardo Fernandes (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
ABSTRACT Purpose: Female sexual dysfunction is a complex and common condition that affects women, and the relationship between sexual function and dyslipidemia is poorly studied. This study aims to assess this relationship in the reproductive life women in the menacme who use combined oral contraceptives (COCs) . Methods: A total of 49 healthy women who were sexually active received COC pills that contained ethinylestradiol 30 mcg (EE30) plus levonorgestrel 150 mcg (LNG150). The women were divided into two groups according to their lipid profiles. Dyslipidemia was defined as a high-density lipoprotein (HDL) level < 50 mg/dL or a low-density lipoprotein (LDL) level > 130 mg/dL. Sexual function was assessed using the Female Sexual Function Index (FSFI) Questionnaire. Lipid and lipoprotein parameters were obtained at baseline and after the sixth cycle. Results: After six cycles of the COCs, the total cholesterol and LDL cholesterol levels in the women with a LDL level > 130 mg/dL decreased by 14.7% and 22.1% respectively. In the women with a HDL level < 50 mg/dL at baseline, the HDL level increased by 15.5% at the end of the study. The arousal and orgasm domains and the FSFI total scores significantly increased in women with and without dyslipidemia. The desire and satisfaction domains increased only in the group without dyslipidemia at the end of the treatment period. Conclusions: The EE30/LNG150 formulation increased the sexual function and it was only positively correlated with the HDL cholesterol level. These data indicated a low correlation between sexual function and the changes in the lipid and lipoprotein metabolism.